Late Age at Menarche Increased Common Carotid Artery Intima-Media Thickness in Overweight and Obese Women - Pietro Scicchitano; Giulia Frasso; Mariangela Carbone; Michele Moncelli; Rosa Carbonara; Franco Silvestris; Giovanni De Pergola; Marco M. Ciccone (Journal of Hypertension and Cardiology, 2013)
Objective: To determine whether age at menarche is an independent predictor of common carotid artery intima-media thickness in overweight and obese adult women. Methods: 403 overweight and obese women, aged 18–72 years, were evaluated. We examined the associations among common carotid artery intima-media thickness (CCA-IMT), age at menarche, body mass index, central fat accumulation (indirectly measured by waist circumference), and other well-known cardiovascular risk factors (blood pressure; fasting serum insulin, glucose and lipids concentrations; insulin resistance (estimated by homeostasis model assessment for insulin resistance)). Results: CCA-IMT was significantly and positively correlated with age (r=0.632, p<0.001), age of menarche (r=0.156, p<0.01), waist circumference (r=0.110, p<0.05), systolic (r=0.292, p<0.001) and diastolic (r=0.183, p<0.001) blood pressure, fasting blood glucose (r=0.265, p<0.001), triglycerides (r=0.204, p<0.001) and total cholesterol (r=0.396, p<0.001) levels. Conversely, CCA-IMT was negatively associated with high-density lipoprotein cholesterol (r=-0.111, p<0.05). Age at menarche was associated with CCA-IMT (r=0.156, p<0.01), age (r=0.110, p<0.05) and waist circumference (r=0.121, p<0.05). Multiple linear analysis showed that only age and age at menarche maintained an independent positive relationship with the CCA-IMT. Conclusions: Age at menarche is positively associated with CCA-IMT, independently of common cardiovascular risk factors (adverse glucose and lipid levels, higher blood pressure,insulin resistance, body fatness and central body fat). Late age at menarche can be considered as an independent cardiovascular risk factor in obese subjects.
Keywords: menarche